Sperm motility and lipid composition in internally fertilizing ocellate river stingray Potamotrygon motoro - Dzyuba, Viktoriya; Sampels, Sabine; Ninhaus-Silveira, Alexandre; Kahanec, Martin; Veríssimo-Silveira, Rosicleire; Rodina, Marek; Cosson, Jacky; Boryshpolets, Sergii; Selinger, Martin; Sterba, Jan; Dzyuba, Borys (Theriogenology, 2019)
All extant groups of Elasmobranches have internal fertilization and the structure of the male reproductive organs is very specific: sperm passes from the internal organs via the cloaca, but the male copulating organ (clasper) is distant from the cloaca. This suggests that sperm can contact the surrounding medium before fertilization. Because of this involvement with the environment, external signaling in sperm motility activation could occur in these species even though their fertilization mode is internal. In this case, spermatozoa of Elasmobranches should hypothetically possess a specific structure and membrane lipid composition which supports physiological functions of the sperm associated with environmental tonicity changes occurring at fertilization. Additionally, sperm motility properties in these taxa are poorly understood. The current study examined sperm lipid composition and motility under different environmental conditions for the ocellate river stingray, Potamotrygon motoro, an endemic South America freshwater species. Sperm samples were collected from six mature males during the natural spawning period. Sperm motility was examined in seminal fluid and fresh water by light video microscopy. Helical flagellar motion was observed in seminal fluid and resulted in spermatozoon progression; however, when diluted in fresh water, spermatozoa were immotile and had compromised structure. Lipid class and fatty acid (FA) composition of spermatozoa was analyzed by thin layer and gas chromatography. Spermatozoa FAs consisted of 33 ± 1% saturated FAs, 28 ± 1% monounsaturated FAs (MUFAs), and 41 ± 1% polyunsaturated FAs (PUFAs), and a high content of n-6 FAs (32 ± 2%) was measured. These results allowed us to conclude that sperm transfer from P. motoro male into female should occur without coming into contact with the hypotonic environment so as to preserve potent motility. In addition, this unusual reproductive strategy is associated with specific spermatozoa structure and lipid composition. Low level of docosahexaenoic acid and relatively low PUFA/MUFA ratio probably account for the relatively low fluidity of freshwater stingray membrane and can be the main reason for its low tolerance to hypotonicity.
Keywords: Animals; motilita spermií; Semen Analysis; Skates, Fish; Sperm Motility; Lipids; analýza spermatu; rejnokovití; mužské pohlaví; Male; zvířata; lipidy